Redes ecológicas: avaliando a interação entre aves frugívoras e plantas em diferentes ambientes de um agroecossistema - Bonifácio, Lorena Santos (Universidade Federal de São Carlos, 2025)
The maintenance of plant diversity depends on the presence of seed dispersers, with birds being the main agents of dispersal in tropical regions. Birds, in turn, rely on plants for resources. However, human-induced disturbances alter ecosystems, negatively affecting species and consequently their interactions. Considering the importance of mutualistic interactions for maintaining the complexity and biological diversity of ecosystems, it is crucial to understand which species and their established interactions persist in altered environments. Therefore, the aim of this study was to understand how bird–plant interactions are structured across different areas of an agroecosystem located on the Lagoa do Sino campus of UFSCar. The study also recorded fruit manipulation, removal, swallowing, and regurgitation behaviors of birds in four environments of the agroecosystem: an Agroforestry System (AFS), forest fragments (a remnant forest and a regenerating forest with abandoned eucalyptus), and an open urbanized area. The results indicate that certain species, such as Thraupis sayaca, Turdus leucomelas, and Dacnis cayana, are essential for the resilience of the agroecosystem. These birds act as ecological connectors by interacting with different groups of plants, such as Cecropia pachystachya, thereby promoting environmental maintenance and balance. The Open Urban Area and Agroforestry System harbor highly attractive plant species that efficiently support the formation of more consistent interaction networks. This pattern is associated with the diversity of available resources and the presence of plant species that bear fruit throughout the year, ensuring the continuous maintenance of ecological interactions.
Ecological networks: evaluating the interaction between frugivorous birds and plants in different environments of an agroecosystem
Keywords: Avifauna; Frugivoria; Interações mutualísticas; Frugivory; Ecological interactions; CIENCIAS BIOLOGICAS::ECOLOGIA; 15. Vida Terrestre